Enhanced hydrolysis of cellulose by catalytic polyethersulfone membranes with straight-through catalytic channels. (December 2019) - Huang, Lilan; Wang, Shaofei; Zhang, Han; Li, Deyuan; Zhang, Yuzhong; Zhao, Lizhi; Xin, Qingping; Ye, Hui; Li, Hong
Graphical abstract: Highlights: The GPMMM with straight-through catalytic channels was fabricated by segregation. The efficient and dynamic continuous-flow hydrolysis of cellulose was realized. The dynamic hydrolysis process is more efficient than static process. The dynamic process alleviates the further degradation of the TRS. The immobilization of GO-SO3 H by polyethersulfone improves its reusability. Abstract: The aim of this study was to prepare sulfonated graphene oxide/polyether sulfone (GO-SO3 H/PES) mixed matrix membranes (GPMMMs) with high porosity and straight-through catalytic channels by segregation and used for dynamic and continuous hydrolysis of cellulose. The high porosity and segregation increased the exposure of catalysts synergistically and the formative GO-SO3 H enriched, straight-through catalytic channels had higher catalytic performance, enhancing the diffusion of hydrolytic products. Dynamic hydrolysis of cellulose is more efficient than static hydrolysis due to the enhanced contact between cellulose and catalysts achieved by the extra driving forces, and the further degradation of produced saccharides was suppressed due to the high freedom of products. The TRS reached 98.18% after 1 h at 150 °C with a catalyst/cellulose mass ratio of 1:5. More importantly, the immobilization of GO-SO3 H by PES improved its stability and reusability at high reaction temperature. This strategy provides guidance to the design of high-performance catalytic membranes.